Cytokinin Growth Responses in Arabidopsis Involve the 26S Proteasome Subunit RPN12 - Smalle, Jan (American Society of Plant Biologists, 2002)
The 26S proteasome is an ATP-dependent eukaryotic protease responsible for degrading many important cell regulators, especially those conjugated with multiple ubiquitins. Bound on both ends of the 20S core protease is a multisubunit regulatory particle that plays a crucial role in substrate selection by an as yet unknown mechanism(s). Here, we show that the RPN12 subunit of the Arabidopsis regulatory particle is involved in cytokinin responses. A T-DNA insertion mutant that affects RPN12a has a decreased rate of leaf formation, reduced root elongation, delayed skotomorphogenesis, and altered growth responses to exogenous cytokinins, suggesting that the mutant has decreased sensitivity to the hormone. The cytokinin-inducible genes CYCD3 and NIA1 are upregulated constitutively in rpn12a-1, indicating that feedback-inhibitory mechanisms also may be altered. rpn12a-1 seedlings also showed changes in auxin-induced growth responses, further illustrating the close interaction between auxin and cytokinin regulation. In yeast, RPN12 is necessary for the G1/S and G2/M transitions of the cell cycle, phases that have been shown to be under cytokinin control in plants. We propose that RPN12a is part of the Arabidopsis 26S proteasome that controls the stability of one or more of the factors involved in cytokinin regulation.